2019
DOI: 10.3847/1538-4357/ab03d3
|View full text |Cite
|
Sign up to set email alerts
|

The First NuSTAR Observation of 4U 1538–522: Updated Orbital Ephemeris and a Strengthened Case for an Evolving Cyclotron Line Energy

Abstract: We have performed a comprehensive spectral and timing analysis of the first NuSTAR observation of the high-mass X-ray binary 4U 1538−522. The observation covers the X-ray eclipse of the source, plus the eclipse ingress and egress. We use the new measurement of the mid-eclipse time to update the orbital parameters of the system and find marginally-significant evolution in the orbital period, withṖ orb /P orb = (−0.95 ± 0.37) × 10 −6 yr −1 . The cyclotron line energy is found approximately 1.2 keV higher than RX… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 62 publications
(121 reference statements)
5
18
0
Order By: Relevance
“…It is therefore of interest to study the CRSF with different instruments at different epochs, and intensity states of the sources. Pulse phaseaveraged and pulse phase-resolved measurements of the CRSF have been carried out previously with AstroSat-LAXPC for 4U 1538-52 (Varun et al 2019) and results were found to be consistent with NuStar measurements (Hemphill et al 2019).…”
Section: Introductionmentioning
confidence: 63%
“…It is therefore of interest to study the CRSF with different instruments at different epochs, and intensity states of the sources. Pulse phaseaveraged and pulse phase-resolved measurements of the CRSF have been carried out previously with AstroSat-LAXPC for 4U 1538-52 (Varun et al 2019) and results were found to be consistent with NuStar measurements (Hemphill et al 2019).…”
Section: Introductionmentioning
confidence: 63%
“…This indicates a trailing accretion stream or wakes from the supergiant companion. A cyclotron resonance scattering feature at around 22 keV has been observed in 4U 1538−52 in detail with Suzaku (Hemphill et al 2014), AstroSat (Varun et al 2019) and NuStar (Hemphill et al 2019).…”
Section: Introductionmentioning
confidence: 91%
“…Clark (2000) and few more observers suggest that the orbit is probably eccentric, with an eccentricity approximately 0.18. This source shows many interesting properties, like significant evolution in the orbital period and cyclotron lines (Hemphill et al 2019) but as stated earlier, our main interest is to do spectroscopic study of the highly ionised X-ray lines.…”
Section: U 1538-522mentioning
confidence: 98%